Carbonylative Suzuki Coupling Reaction Catalyzed by a Hydrospirophosphorane Palladium Complex. Issue 23 (15th November 2017) - Wójcik, Przemysław; Sygellou, Labrini; Gniewek, Andrzej; Skarżyńska, Anna; Trzeciak, Anna
Abstract: A Pd complex with the H‐spirophosphorane ligand, PdCl2 P(OCMe2 CMe2 O)OC6 H4 NH2 (Cat. 1), was used as the catalyst in the carbonylative Suzuki coupling of substituted iodobenzenes with arylboronic acids and with sodium tetraphenylborate. Substituted diarylketones were obtained in good to excellent yields and a selectivity over 95 % under 1 atm of CO with 1.5 mol % of the catalyst. The promoting role of the H‐spirophosphorane ligand in the catalytic process was evidenced. We used X‐ray photoelectron spectroscopy, TEM, and 31 P NMR spectroscopy to reveal that during the reaction Cat. 1 undergoes transformation into Pd complexes that bear the spirophosphorane ligand or other P ligands formed by its dealkylation and to Pd nanoparticles. All these Pd species contribute to the high productivity of the system. Abstract : Cocktail hour : The "cocktail‐type" catalytic system that contains Pd complexes and Pd nanoparticles with the H‐spirophosphorane ligand is highly efficient in carbonylative Suzuki coupling under mild conditions.